Improvisación Teatral Para La Escena Como Espacio Creativo (2013)
The project “THEATRAL IMPROVISATION FOR THE SCENE AS A SPACE CREATIVE‟ was developed with the purpose of achieving two key objectives, the which seek the answer to the concerns presented, about the actor and his preparation for the scene, in this way a work was created, which I take as referring to the theater, the elements of training for the actor, the which sought to develop a dramatic text through improvisation, and in Consequently, the development of a written analysis of the process obtained with the elements that were constituted in the dramaturgy for the work.